KETERGANTUNGAN KONTEN INSTAN DAN RISIKO POPCORN BRAIN PADA ANAK - M. Fauzan Naufal. S; Munisa; Rizkina Amalia; Kasih Anggraini; Indah Agutin (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Rapid advancements in digital technology over the past five years have significantly altered information consumption patterns, particularly among children. Easy access to instant content—such as short-form videos and algorithm-driven social media—accustoms children to repetitive, rapid stimulation. This phenomenon has given rise to the term